Successful Pregnancy in Uncorrected Tetralogy of Fallot with Right Aortic Arch: An Interdisciplinary Team Approach - Millisani, Hayla Iqda; Putri, Valerinna Yogibuana Swastika (Heart Science Journal, 2024)
Background: Tetralogy of Fallot (ToF) is the most common cyanotic disorder, with a global prevalence of congenital heart disease nearly reaching 10%. The anomalies observed in individuals with ToF result from the anterior and cephalad displacement of the infundibular (outflow tract) component of the interventricular septum. ToF continues to be a significant contributor to maternal morbidity, mortality, and adverse outcomes in newborns with the condition.Case presentation: An 18-year-old woman in her 28th week of pregnancy was referred to our tertiary referral center, Saiful Anwar Hospital, diagnosed with uncorrected Tetralogy of Fallot (TOF), which had been noticed since she was 2 years old. At that time, her parents refused treatment. She became pregnant unexpectedly and was then directed to RSSA for further management.Conclusion: We present a successful case of pregnancy in a woman who has not undergone surgical repair for ToF. An interdisciplinary pregnancy heart team, including a cardiologist, obstetrician, anesthesiologist, midwives, and neonatologists at our tertiary hospital, developed a care plan based on an individualized assessment of the patient's comorbidities and ToF. The life expectancy of this pregnant woman and her baby is higher with a team approach. The choice of contraception and family planning should be part of the discussion and follow-up from the teenage years, allowing patients with ToF to control their fertility and make informed decisions about having children.